The Future of National Security Law: Urgence and Ideas - Kriswanto, Kriswanto; Rizqi, Alda Rifada; Huda, Muhammad Maftahul (SASI, 2023)
Introduction: Sishankamrata is Indonesia's defence and security system that optimizes all nation components to maintain its existence. Sishankamrata emphasizes the collaboration and participation of citizens and related institutions. However, there was a legal vacuum before the National Security Law was enactedPurposes of the Research: This study seeks to discuss and analyze the urgency of the formation of the National Security Law to make the implementation of Sishankamrata successful.Methods of the Research: This research is normative legal research with a statutory and conceptual approach. The legal materials in this study include the 1945 Constitution of the Republic of Indonesia and the law governing national defence as the primary legal material. Secondary legal materials include books, articles, and research results. Non-legal materials include all non-legal studies related to national defence.Results of the Research: The results of the study confirm that the legal vacuum of the National Security Law needs to be overcome with the immediate ratification of the Law by emphasizing the urgency of enacting the Law through political will between the President and the DPR. In the future formulation, the Law must be reviewed formally and materially, especially by involving community participation and substantively guaranteeing the rights of the community in Sishankamrata.